2021
DOI: 10.3390/ijerph182111436
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Correlates of COVID-19 Worry: Stigma, Knowledge, and News Source

Abstract: Non-adherence to COVID-19 guidelines may be attributable to low levels of worry. This study assessed whether endorsing COVID-19-stigmatizing restrictions, COVID-19 knowledge, and preferred news source were associated with being ‘very worried’ versus ‘not at all’ or ‘somewhat’ worried about contracting COVID-19. Survey data were collected in July–August 2020 from N = 547 New York State (NYS) and N = 504 national Amazon MTurk workers. Respondents who endorsed COVID-19 stigmatizing restrictions (NYS OR 1.96; 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 83 publications
(61 reference statements)
4
20
0
Order By: Relevance
“…Throughout the pandemic, although resources were scarce, new tools and strategies were developed. One of these strategies was the development of guidelines to prevent the spread of COVID-19, which included promoting social distancing, handwashing, mask wearing, frequent testing and vaccination [ 5 ]. These guidelines are not always well received by the public, which posed a challenge for successfully preventing disease spread [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Throughout the pandemic, although resources were scarce, new tools and strategies were developed. One of these strategies was the development of guidelines to prevent the spread of COVID-19, which included promoting social distancing, handwashing, mask wearing, frequent testing and vaccination [ 5 ]. These guidelines are not always well received by the public, which posed a challenge for successfully preventing disease spread [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of these strategies was the development of guidelines to prevent the spread of COVID-19, which included promoting social distancing, handwashing, mask wearing, frequent testing and vaccination [ 5 ]. These guidelines are not always well received by the public, which posed a challenge for successfully preventing disease spread [ 5 ]. Meltzer et al found that adherence to public health measures was related to worry about contracting COVID-19 [ 5 ], and in a study of Reader et al, at least 17–21% of the respondents were not likely at all to wear a mask [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations